Virtual sexperience the influence of online socialization on sexual attitudes of UPLB students from Catholic High Schools - Milan, Jamie Nicole San Buenaventura (Lagom: Compendium of CAS Undergraduate Research Abstracts, 2021)
Comprehensive sex education is crucial in ensuring a happy and safe sex experience. However, the massive influence of the Catholic church in the country is seen as one of the barriers to the delivery of comprehensive sex education especially in Catholic schools (Nichols, 2020: Lasco, 2017); Austria, 2010; Palatino, 2010). With the status of the Philippines as the world's social media as an information source for sex education, particularly on the interpersonal aspects of sex.